EEG data and introspective reports from the Libet׳s experiment replication - Dominik, Tomáš; Dostál, Daniel; Zielina, Martin; Šmahaj, Jan; Sedláčková, Zuzana; Procházka, Roman (Data in brief, 2018)
This article provides data from a contemporary replication of Libet׳s experiment. For the methodology, results and discussion of the replication, see the article "Libet׳s Experiment: A Complex Replication" (Dominik et al., 2018). Three types of data are presented in this article: (1) introspective reports (M, W and S), (2) EMG onset times relative to a mouse click or to the target time in tasks with a movement at pre-set time and (3) relevant averaged EEG data.